An Overview of Important Ethnomedicinal Herbs of Phyllanthus Species: Present Status and Future Prospects - Bharti Sarin; Nidhi Verma; Juan Pedro Martín; Aparajita Mohanty (The Scientific World Journal)
The genus Phyllanthus consists of more than 1000 species, of which many are used as traditional medicines. The plant extracts have been used since ancient times, for treating hypertension, diabetes, hepatic, urinary, and sexual disorders, and other common ailments. Modern day scientific investigations have now confirmed pharmacognostic properties of Phyllanthus herbs. The phytochemicals attributing these medicinal properties have been identified in many of the Phyllanthus herbs. The morphologically similar herbs of Phyllanthus grow together and admixture of species during collection for manufacture of herbal medicines is quite common. Hence, along with pharmacognostic and phytochemical studies, appropriate protocols for correct identification of species are also important. As the use of these herbs as green medicines is becoming more popular, it is imperative to assess its genetic diversity and phylogenetic relatedness for future conservation strategies. This review is an attempt to present an overview of the existing studies on pharmacognostics, phytochemistry, species identification, and genetic diversity of Phyllanthus herbs and consequently (i) highlight areas where further research is needed and (ii) draw attention towards extending similar studies in underutilized but potentially important herbs such as P. maderaspatensis, P. kozhikodianus, P. rheedii, P. scabrifolius, and P. rotundifolius.